EXPLORING TEACHERS’ PERCEPTION AND EXPERIENCE OF TEACHING ENGLISH SPEAKING SKILL THROUGH VIRTUAL MEETING IN HIGHER EDUCATION - Insani Nurchintyawati; Nurul Ilmi; Pujalinda Mandarsari; Syauqiyah Awaliyah Alfiani Nur (Institut Agama Islam Negeri (IAIN) Bone, 2023)
Virtual education has exploded in recent years and become even more central to university and school life globally, especially with the advent of Covid-19. With the rise in popularity of virtual meetings, an increasing number of teachers use them to teach English speaking as an alternative to face-to-face instruction. This article examines the attitudes of teachers and the features of virtual meeting platforms that help and hinder the teaching of speaking skills. The study was conducted at several universities in South Sulawesi, Indonesia, based on a survey of twelve teachers. Seven teachers have recognized virtual meetings for their positive attitudes toward their use in teaching English speaking. Virtual meeting applications raise the most critical concerns regarding limited expression and limited variation. The most popular platforms among teachers are Zoom and Google Meet.